2022
DOI: 10.1002/saj2.20369
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary assessment of the space‐for‐time substitution method in soil carbon change prediction

Abstract: Prediction of the soil C response to environmental change is often limited by the absence of temporal soil monitoring data from which applicable models can be developed. This constrains the understanding of the processes governing soil C cycling in data‐poor areas. Here, we demonstrate a method to predict soil organic C (SOC) change over time based on the space‐for‐time (SFT) substitution method by constructing spatial and temporal datasets of SOC change from soil datasets pertaining to four periods over the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Due to the very short duration of these time series, the mean annual temperature of most sites only varied by a few degrees Celsius within a site, strongly limiting the ability of this dataset to discern any relationship. This weak statistical power is accentuated by the lack of additional relevant explanatory variables, such as vegetation and soil water content 8 . We hope that additional datasets will be available in the future to clarify these relationships.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the very short duration of these time series, the mean annual temperature of most sites only varied by a few degrees Celsius within a site, strongly limiting the ability of this dataset to discern any relationship. This weak statistical power is accentuated by the lack of additional relevant explanatory variables, such as vegetation and soil water content 8 . We hope that additional datasets will be available in the future to clarify these relationships.…”
mentioning
confidence: 99%
“…On the contrary, SFT is often used in ecological studies and can provide valuable mechanistic insights 9 . Especially Yang et al 8 found high validity in the SFT approach for modeling soil carbon processes. Most importantly, we disagree with the rationale of the approach taken by Yue et al to test for SFT biases, and question how bootstrapping can be used for that purpose.…”
mentioning
confidence: 99%
“…However, the overwhelming majority of DSM studies ignore time. This is because spacetime mapping of soil properties remains a major challenge, with relatively few studies having mapped temporal changes and mostly only at the field scale (Meersmans et al, 2011(Meersmans et al, , 2016Sun et al, 2012;Stockmann et al, 2015;Gasch et al, 2015;Minasny et al, 2016;Gray & Bishop, 2016Yigini & Panagos, 2016;Schillaci et al, 2017;Hengl et al, 2017a;Sanderman et al, 2017;Song et al, 2018;Stumpf et al, 2018;Reyes Rojas et al, 2018;Adhikari et al, 2019;Huang et al, 2019;Zhou et al, 2019;Heuvelink et al, 2020;Sun et al, 2021;OpenGeoHub et al, 2022;Yang et al, 2022). These studies have used various space-time modelling approaches.…”
Section: Space-time Mapping In 3d+tmentioning
confidence: 99%
“…Another approach is space-for-time-substitution (e.g. Adhikari et al, 2019;Yang et al, 2022), although differences in a dynamic soil property due to temporal changes are not necessarily comparable to differences due to spatial variation. Commonly, soil property changes are mapped using a static model, by simply replacing covariates such as land use or climate during prediction with a historic map or future scenario (Yigini & Panagos, 2016;Meersmans et al, 2016;Gray & Bishop, 2016Adhikari et al, 2019;Huang et al, 2019;Reyes Rojas et al, 2018).…”
Section: Space-time Mapping In 3d+tmentioning
confidence: 99%